(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article explores the poetics of science fiction in 21st-century American literature, focusing on the works of William Gibson and Neal Stephenson. Both authors engage with critical themes such as technology, identity, and ethics, offering distinct yet complementary perspectives on humanity’s evolving relationship with innovation. Gibson’s introspective narratives often depict alienation and fragmented identities in hyper-mediated worlds, emphasizing the limitations of agency under systemic forces. In contrast, Stephenson’s expansive storytelling highlights technological ambition, interconnectivity, and the moral dilemmas of innovation, celebrating human ingenuity while interrogating its consequences. By comparing their approaches to shared themes like alienation, agency, and the ethical implications of progress, this study illuminates how Gibson’s atmospheric poetics and Stephenson’s grand narratives offer a rich exploration of the human condition in technologically transformed landscapes. Ultimately, their works challenge readers to consider the balance between technological potential and ethical responsibility, underscoring the enduring quest for meaning and connection in a rapidly changing world